Greek Identity in the Western Mediterranean : Papers in Honour of Brian Shefton - Shefton, Brian B.; Lomas, Kathryn, 1960- (Mnemosyne, Supplements, 2004)
The Greek colonies of the Western Mediterranean were central to the evolution of many aspects of Greek culture and in many cases developed an identity which was significantly different from that of mainland Greece and the Aegean. This volume seeks to explore aspects of the cultural identity of these colonies and how it evolved. It covers the colonial foundations in Italy, Sicily, Southern France, Spain and North Africa, and ranges from the 8th century BC to the early Roman empire. Topics covered include the ethnic identity of the earliest colonial foundations, the evolution of Greek states in the West, the Greeks' perceptions of their own identity and ways of representing it, and the role of the indigenous populations in the evolution of Western Greek culture.